Highly efficient removal of pharmaceuticals from water by well-defined carbide-derived carbons - Álvarez-Torrellas, Silvia; Munoz, Macarena; Gläsel, Jan; de Pedro, Zahara M.; Domínguez, Carmen M.; García, Juan; Etzold, Bastian J.M.; Casas, Jose A. (Chemical Engineering Journal, 2018)
In this work, we evaluate the feasibility of carbide-derived carbons (CDCs) as reliable and highly efficient adsorbents for the removal of pharmaceuticals from water. CDCs were produced from titanium carbide at temperatures within the range of 800–1400 °C employing chlorine as extraction agent. The materials were physicochemically characterized and tested in the adsorption of two relevant pharmaceuticals (diclofenac (DCF) and metronidazole (MNZ)) in aqueous solutions. We found that the specific surface area in combination with a low functionalized surface plays a key role on the adsorption capacity of the material while the average pore size determines the kinetics of the process. Notably, the CDCs showed an outstanding adsorptive behaviour compared to different conventional carbon materials under the same operating conditions, which was attributed not only to their high surface areas but mainly to their strong hydrophobic properties. The optimum material (specific surface area of 1676 m2 g−1) showed extremely high adsorption capacity values (551 and 410 mg g−1 for DCF and MNZ, respectively). Remarkably, the process was very fast (10 min of equilibrium time) even using low doses of adsorbent (0.3 mg mL−1). The performance of the optimum CDC was also demonstrated in bi-component systems while its versatility was demonstrated in a real wastewater treatment plant (WWTP) effluent, obtaining a good performance in terms of adsorption capacity (up to ∼400 mgDCF g−1) and kinetics (equilibrium time of 10 min). These results demonstrate the promise of CDCs for reliable, effective and fast flow-through tertiary water treatment.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Adsorption; Carbide-derived carbons; Pharmaceuticals; Water treatment